Genipin induces mitochondrial dysfunction and apoptosis via downregulation of Stat3/mcl-1 pathway in gastric cancer - Min Jee Jo; Soyeon Jeong; Hye Kyeong Yun; Dae Yeong Kim; Bo Ram Kim; Jung Lim Kim; Yoo Jin Na; Seong Hye Park; Yoon A Jeong; Bu Gyeom Kim; Hassan Ashktorab; Duane T. Smoot; et al. (2019)
Genipin is a compound derived from gardenia fruit extract. Although Genipin has anti-tumor effects in various cancers, its effect and mechanism in gastric cancer remain unclear. Here, we investigated the relationship between the anticancer effect of Genipin and signal transducer and activator of transcription (Stat3)/myeloid cell leukemia-1 (Mcl-1) in human gastric cancers.MTT assays were performed to determine the cell viability of gastric cancer and gastric epithelial cell lines (AGS, MKN45, SNU638, MKN74, HFE-145). A TUNEL assay and Western blotting were carried out to investigate apoptosis. Stat3 activity was measured by proteome profiler phospho kinase array, immunofluorescence and immunoblotting. Mitochondria function was monitored with an XF24 analyzer and by flow cytometry, confocal microscopy using fluorescent probes for general mitochondrial membrane potential (MMP).Genipin induced apoptosis in gastric cancer cells, including AGS and MKN45 cells. Genipin also reduced Mcl-1 mRNA and protein levels. Furthermore, we found that phosphorylation of Stat3 is regulated by Genipin. Additionally, the protein level of phospho Janus kinase 2 (JAK2) was decreased by Genipin treatment, indicating that the Stat3/JAK2/Mcl-1 pathway is suppressed by Genipin treatment in gastric cancer cells. Mcl-1 is closely related to mitochondrial function. These findings suggest that Genipin contributes to the collapse of mitochondrial functions like MMP.Genipin induced apoptosis by suppressing the Stat3/Mcl-1 pathway and led to mitochondrial dysfunction. Our results reveal a novel mechanism for the anti-cancer effect of Genipin in gastric cancer.